The Numerical Prediction of Flow of Branched Polymer Melts Through Planar Contraction Channel by Finite Element Method - H.A. Khalaf (University of Thi-Qar Journal, 2019)
In this work we present an investigation of a complex viscoelastic flow through an abrupt expansion with expansion ratio D/d = 4, where the Oldroyd-B model was consider as a constitutive equation. The governing equations are solved using the Finite Element Method. The polymer is modeled as a monodisperse suspension of “Oldroyd-B” molecules, which provides a direct link the molecular topology and the flow properties of the melt. The branching produces an enhancement in the size of upstream vortex in creeping flows. Also was found that including inertia forces will give the intensity of lip vortex increases, while the size of corner vortex will initially decreased with growth of Weissenberg number but with more increase (We>4), the size of corner vortex will begin to increase in size. The effect arises from the differing responses in shear and extensional flows of polymer melts.